A Study On The Cohesion Devices Employed In The Songs Of Michael Learn To Rock (MLTR) Group Of Music's - Afandi, Noor (2004)
There are two problems in this study: (1) What are the cohesion devices used by MLTR Group of music's in song lyric writing? (2) How the cohesion devices support the couplet coherence? The writer uses documentary technique in collecting the data and simple random sampling which he uses lottery procedure to get the data. In analyzing the texts of song, the writer bases on the cohesion devices and the formula of paragraph. The cohesion devices consists of pronoun, repetition and transition, and the formula paragraph consists of a topic, restriction and illustration. The result of this study shows that the cohesion devices which consist of pronoun, repetition, and conjunction are applied in the texts of MLTR songs. Those three types of cohesion devices and the formula of paragraph are applied in those songs to create them coherence couplets, compact and unity; and those couplets are written to explain a single idea, this idea contained a single line as topic line. There are six songs in this analysis. They consist of 36 couplets and 160 lines, 30 couplets are coherence and 6 couplets are incoherence, and 28 couplets are related to the formula of paragraph and 8 couplets are unrelated to the formula of paragraph.